Neuroendocrine Rectal Tumors: Main Features and Management - Rodrigues,Ângela (2015)
The incidence of neuroendocrine tumors of the rectum has been increasing in the last decades, partly due to improved investigation. They are mostly well-differentiated small tumors with a rather good overall prognosis. In the last few years, some aspects of neuroendocrine tumors have been evolving. In 2010, the World Health Organization proposed a new classification, indicating that these tumors, as a category, should be considered malignant. Afterwards the European Neuroendocrine Tumor Society published their guidelines for the management of colorectal neoplasms. Treatment algorithm is mainly based on tumor size and grading and, in general, well-differentiated rectal tumors <2 cm can be endoscopically resected. Endorectalultrasound plays a particularly important role by accurately assessing tumor size and depth of invasion prior to resection. There are no specific recommendations on the optimal endoscopic resection method, but data from recent studies suggests that modified endoscopic mucosal resection techniques and endoscopic submucosal dissection have superior complete resection rates.